Disciplining geo-body of the Dutch Indies: discourse analysis on the colonial school textbooks of Geography - Dhona, Holy Rafika (Penerbit Universiti Kebangsaan Malaysia, 2019)
Geography was one of the instruments the Dutch used to master the knowledge about their colonial possessions. In the Dutch Indies, geographical knowledge was developed by the Dutch colonial government and introduced to the natives through schools. The school textbooks in the Dutch colonial periods were important media for disseminating the modern geography knowledge to the natives. By analysing three geography textbooks from 1875 to 1920, this paper examines how was a new spatial mode portrayed and disseminated through colonial textbooks of geography, and how did modern geography build a new subjectivity among the colonized society. Applying Foucauldian discourse analysis, this paper aims to explicate the roles of media in producing a new spatial mode in the Dutch Indies. This study finds that geography textbooks have introduced the Hindia Netherland as a single entity under the Dutch colonial power. The textbooks, as the narrative explanation of the map, have legitimized the map as an established truth. Not only trained the natives how to read the maps, they have also trained the natives how to make the maps. They have constructed a new mode of spatiality, through which the natives were perceived as individuals, placed in and belong to certain territories, no longer related to certain rulers. The modern geography was the perfect instrument of colonial epistemological domination. It has emerged as a new knowledge or power of humans and their regions, through which the Dutch colonial government has changed the traditional ‘mandala’ form of power into a modern ‘geo-body’ form